ChemInform Abstract: Direct Access to 2‐Amino‐5‐azidomethylfurans Through Palladium‐Catalyzed Azidative Cycloisomerization of Homoallenyl Amides. Issue 52 (6th December 2016) - Huang, Qianwen; Zheng, Hanliang; Liu, Shuiyou; Kong, Lichun; Luo, Fang; Zhu, Gangguo
Abstract: A novel azidative cycloisomerization of homoallenyl amides (I) and (III) using TmsN3 as the azidation reagent and a hypervalent iodine reagent as the oxidant giving a series of azidomethyl‐furans (II) and (IV), resp., is presented.